Effect of salt stress on growth of sorghum germplasms at vegetative stage (Journal of the Bangladesh Agricultural University, 2018)
Soil salinity is an increasing problem in the world and main obstacle to agricultural productivity especially in areas where irrigation is necessary. It adversely affects plant growth and development. Adoption of salt tolerant variety is more important here and so screening of salt tolerant germplasms is essential. For this reason, a germination test under salinity and a hydroponic experiment were conducted at Plant Physiology Laboratory, Department of Crop Botany, Bangladesh Agricultural University, Mymensingh to investigate the effect of NaCl on germination, morphological characters and growth of sorghum seedlings. The experiment comprised of two levels of NaCl concentration viz. Control (without NaCl and EC 1.36 dSm−1 in hydroponic culture) and 80 mM NaCl and five sorghum germplasms viz. BD 700, BD 703, BD 707, BD 710 and BD 726. There were 10 (5×2) treatments in a completely randomized design (CRD) with three replications. Results showed that germination percentage, hypocotyls and epicotyls length, root and shoot length, leaf length, leaf sheath length, fresh and dry mass production were influenced by NaCl stress. However, among tested germplasms, BD 707 showed the best performance considering the seedlings growth, germination percentage and other parameters. BD 710 and BD 703 showed the highest sensitivity to NaCl stress based on the above parameters studied. These results suggested that sorghum is able to grow with moderate salinity.J. Bangladesh Agril. Univ. 16(1): 67-72, April 2018